A study of the influence of plasma post-oxidizing on the corrosion resistance. (January 2015) - Wu, Jiqiang; Ye, Xuemei; Li, Hu; Hu, Jing
Abstract: AISI 4140 steel was selected as the material and plasma post-oxidation by plain air in the same nitriding system just after plasma nitriding was investigated primarily. The results show that a thin oxide layer composed of Fe3 O4 and Fe2 O3 is formed, and the ratio of Fe3 O4 to Fe2 O3 is closely related to the plasma post-oxidizing temperature and time. The highest ratio of Fe3 O4 to Fe2 O3 is obtained while post-oxidizing at 673 K for 60 min due to lower standard Gibbs free energy and appropriate forming rate for the formation of Fe3 O4 at this condition. The thin oxide layer brings out significant improvement of corrosion resistance, especially at higher ratio of Fe3 O4 to Fe2 O3 . Surface images of the corroded specimens after polarization test shows that there exists no corrosion pit for the specimen post-oxidized at 673 K for 60 min, though some corrosion pits exist for those treated under other conditions. Highlights: Plain air was primarily used for plasma post-oxidation for AISI 4140 steel. A thin iron oxide layer composed of Fe3 O4 to Fe2 O3 was formed on top of the compound layer. The ratio of Fe3 O4 to Fe2 O3 was depended on plasma post-oxidizing temperature and time. Highest ratio of Fe3 O4 to Fe2 O3 brought out optimum corrosion resistance.